2022
DOI: 10.1101/2022.08.06.503061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myocardial deformation imaging by 2D speckle tracking echocardiography for assessment of diastolic dysfunction in murine cardiopathology

Abstract: Diastolic dysfunction is increasingly identified as a key, early onset subclinical condition characterizing cardiopathologies of rising prevalence, including diabetic heart disease and heart failure with preserved ejection fraction (HFpEF). Diastolic dysfunction characterization has important prognostic value in management of disease outcomes. Validated tools for in vivo monitoring of diastolic function in rodent models of diabetes are required for progress in pre-clinical cardiology studies. 2D speckle tracki… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…This dietary regime employed in this study has been well characterized as a model of diastolic dysfunction, with gradual development of metabolic disturbance (stable rate of weight gain and mild hyperglycemia), with maintained systolic function (ejection fraction and fractional shortening). As has been reported previously, over the time span of the dietary intervention differential fibrosis is not observed (Daniels et al, 2022;Wells et al, 2023;data not shown).The data presented here are consistent with clinical observations linking cardiometabolic disease and diastolic dysfunction.…”
Section: Dietary Model Of Acquired Metabolic Syndrome and Cardiac Dia...supporting
confidence: 93%
See 2 more Smart Citations
“…This dietary regime employed in this study has been well characterized as a model of diastolic dysfunction, with gradual development of metabolic disturbance (stable rate of weight gain and mild hyperglycemia), with maintained systolic function (ejection fraction and fractional shortening). As has been reported previously, over the time span of the dietary intervention differential fibrosis is not observed (Daniels et al, 2022;Wells et al, 2023;data not shown).The data presented here are consistent with clinical observations linking cardiometabolic disease and diastolic dysfunction.…”
Section: Dietary Model Of Acquired Metabolic Syndrome and Cardiac Dia...supporting
confidence: 93%
“…4G). To evaluate possible influence of mechanical state on the Ca As we have reported previously, over the time span of the dietary intervention differential fibrosis is not observed (Daniels et al, 2022;Wells et al, 2023). The finding of increased stiffness in cardiometabolic disease is consistent with some aspects of prior experiments involving animal feeding of obesogenic diets, using other rodent preparation types -including permeabilized cardiomyocytes, tissue strips/papillary muscles, and non-paced cardiomyocytes (Leopoldo et al, 2010;Gonçalves et al, 2016;Sowers et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation